PENGARUH EFEKTIVITAS KOMITE AUDIT, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP PEMILIHAN AUDITOR EKSTERNAL (Studi Empiris Pada Perusahaan Manufaktur Terdaftar di BEI Tahun 2014-2016) - Alfian, Nurul; Suryansyah, AH (JURNAL AKUNTANSI DAN INVESTASI, 2017)
One of the qualitative characteristics of accounting information is reliability. The way to maintain the reliability of the financial statements is to use audit services on financial statements. The auditor as the party responsible for reporting financial information must have adequate competence, uphold independence and professional and ethical behavior so that the result of his work can be trusted its relevance and reliability. The objective of this study is to analyze the influence of audit committee, company size, and leverage on the choice of external auditor. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2014-2016. This study used big four and nonbig four auditor clasification as a proxy of audit quality that will be chosen by the company. The sample was determined by the method of purposive sampling to obtain a sample of 32 companies. Testing the hypothesis using multiple regression analysis. The results of hypothesis testing indicate that auditee commitee, Company size, had a significant positiff effect on the choice of external auditor. Instead leverage had not influence on the choice of external auditor.